Activity of Sea Cucumber and Spirulina in Wound Healing and Blood Glucose Decreasing in Streptozotocin- Induced Diabetic Rats - Susanto Hendra; Safithri Mega; Tarman Kustiariyah; Setyaningsih Iriani (BIO Web of Conferences, 2024)
Previous study showed that sea cucumber and spirulina had an antioxidant activity and antihyperglycemic activity. Sea cucumbers contain a cell growth factor that is useful in wound healing. This research aimed to determine the activity of sea cucumber and spirulina in decreasing the fasting blood glucose and wound healing process in streptozotocin-induced diabetic rats. The antihyperglycemic activity and wound healing test were done to experimental rats that have been conditioned with diabetic wound. 2840 mg/kg body weight of liquid preparation of sea cucumber methanol extract and 81 mg/kg body weight of spirulina extract were given through oral gavage and sea cucumber methanol extract was given topically once a day. The results showed that group of golden sea cucumber orally-topically had the best antihyperglycemic activity with the highest percentage reduction in blood glucose level while group of golden sea cucumber topically-spirulina orally had the best wound healing effect with the highest percentage of wound healing.